2011
DOI: 10.1016/j.neuropsychologia.2011.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Visuotactile interactions in the congenitally acallosal brain: Evidence for early cerebral plasticity

Abstract: a b s t r a c tStudies in patients with an isolated, congenital agenesis of the corpus callosum have documented potentials and limits of brain plasticity. Literature suggests that early reorganization mechanisms can compensate for the absence of the corpus callosum in unisensory tasks that involve interhemispheric transfer. It is unknown, however, how the congenitally acallosal brain processes multisensory information, which presumably requires interhemispheric transfer of modality-specific input. Therefore, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…This means that the brain has access to postural information, and cortical structures like the posterior parietal cortex (PPC) have been shown to be a key player in integrating postural with sensory information (Azanon et al 2010b). However, cross-modal effects are usually smaller when the arms are crossed Maravita et al 2002;Spence and Walton 2005;Wolf et al 2011) and early mapping mechanisms (Ͻ60 -80 ms) do not take posture into account (Azanon and Soto-Faraco 2008;Overvliet et al 2011). In line with this, and based on the delays inherent to interhemispheric remapping, we had predicted that multisensory integration would be less effective for the crossed posture than that for the default posture, due to the temporal principle.…”
Section: Discussionmentioning
confidence: 99%
“…This means that the brain has access to postural information, and cortical structures like the posterior parietal cortex (PPC) have been shown to be a key player in integrating postural with sensory information (Azanon et al 2010b). However, cross-modal effects are usually smaller when the arms are crossed Maravita et al 2002;Spence and Walton 2005;Wolf et al 2011) and early mapping mechanisms (Ͻ60 -80 ms) do not take posture into account (Azanon and Soto-Faraco 2008;Overvliet et al 2011). In line with this, and based on the delays inherent to interhemispheric remapping, we had predicted that multisensory integration would be less effective for the crossed posture than that for the default posture, due to the temporal principle.…”
Section: Discussionmentioning
confidence: 99%
“…However, because stimuli that are presented at the same hand map onto different hemispheres in the crossed hand posture, processing of such multisensory stimuli involves interhemispheric crosstalk (Spence et al, 2001a,b). Accordingly, other studies have suggested that crossing the hands may lead to intermediate effects (Maravita et al, 2002; Spence and Walton, 2005; Wolf et al, 2011). …”
Section: Discussionmentioning
confidence: 97%
“…The idea of a predominance of external spatial integration (requiring interhemispheric transfer) over intrahemispheric integration is supported by the findings from a study in which the CCE was determined entirely by proximity of tactile and visual stimuli in external space (Spence et al, 2004). While other studies in healthy participants reported more similar CCE scores for same-side and different-side stimulus pairs in the crossed posture (Maravita et al, 2002; Spence and Walton, 2005; Wolf et al, 2011), Spence et al (2001a,b) demonstrated in a split-brain patient that an intact corpus callosum is necessary for spatial remapping across hemispheres. Moreover, a recent developmental study showed that children younger than five and a half years did not display a crossed hand effect in the temporal order judgment task, possibly indicating that maturation of the corpus callosum is a prerequisite for spatial remapping (Pagel et al, 2009).…”
Section: Introductionmentioning
confidence: 89%
“…Indistinguishable CCEs for uncrossed and crossed hand posture conditions have previously been demonstrated and have generally been interpreted as evidence for an exclusive activation of external coordinates during visual–tactile integration (Spence et al ., ; Experiment 3). However, modulations of the CCE by hand posture have previously been observed and have been suggested to reflect the concurrent activation of somatotopic and external coordinates (Spence & Walton, ; Wolf et al ., ). In line with this idea and recent evidence on weighted reference frame integration (Badde et al ., , ), we hypothesise that the specific task demands of our experimental design resulted in a stronger weighting of the somatotopic coordinates compared with the classical cross‐modal congruency design.…”
Section: Discussionmentioning
confidence: 97%